EVALUASI KURIKULUM BAHASA ARAB DI SMP IT JAISYUL QUR’AN BANDUNG - Misbahul Munir, Hildan (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Evaluation of the curriculum of the Arabic language program in schools is very important to ensure that the program is in accordance with the educational objectives that have been set.The purpose of this study was to determine the structure of the Arabic curriculum at SMP it Jaisyul Qur'an Bandung. This study is a field research (field research), with the type of qualitative descriptive research. The type of data collection used is direct research on the object under study using triangulation method data collection method consisting of observation, interviews and documentation. The results showed that the structure of the curriculum at SMP it Jaisyul Qur'an integrated culturally with Islamic boarding school education. The purpose of learning includes all aspects in the field of Arabic, especially pressing on improving the ability to understand the teachings of Islam. The content of the material consists of language skills, language science and Islamic Studies in Arabic. The methods used vary according to the target of learning and learning media include audio, visual and audio visual media. The evaluation and assessment system generally consists of written, oral and practical tests. Teacher qualifications must be based on educational background and have scientific capacity in the Arabic language.